Persepsi Wajib Pajak di Wilayah Tangerang Terhadap Digitalisasi Pelaporan Pajak - Nadya Regina Louis; Stefanus Ariyanto (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2021)
The use of technology in tax administration is part of the efforts of the Directorate General of Taxes to assist taxpayers in the tax reporting and payment process. One of them is by using the e-Filing application. The aim of this study is to examine the taxpayer perception in explaining the digitalization of tax reporting systems using e-filing applications in the Tangerang area. The study uses usefulness, user satisfaction, ease of use, and security/confidentiality perceptions as proxies to the taxpayer perception. Samples of this study are taken using the convenience sampling method consist of 106 respondents in the Tangerang area, analyzed using the multiple linear regression method. The result of this study reveals that usefulness and user satisfaction perception has a significant impact on taxpayer perception on using e-filing systems, while ease of use and security/confidentiality perception doesn’t have a significant impact on taxpayer perception of using the e-filing systems.